Land Control and Ideological Struggle: Competing Articulations of âThe Owner of Landâ - Savitri, Laksmi Adriani (Departement of Communication and Community Development, 2013)
The implementation of large scale industrial farming investment involves land deals that are not only being navigated through regulated practices, but state and non-state actors also employ a strategy to âgrip the minds of the massesâ to enable the deals. âGripping the mindsâ involves articulatory practices within the terrain of ideological struggle, which put land deals always in process. This paper argues that âthe owner of landâ as a cultural identity that was constructed historically by determining forces, and not confined merely as form of rights, is articulated in three competing positionings toward land deals: rejection, renegotiation and acceptance. The state and non-state actors or NGOs broker the process of identification toward modernism by constructing representations of capital as the good and bad Other. These representations of capital provide âlogicâ which connected meanings of modernism with âthe owner of landâ identity. âGripping the mind of the massesâ to smoothen land deals involves correspondences as well as non-correspondences between modernism and the Marind identity of Anim-ha that render connected chain of meanings unstable. Â© 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keyword: land control, land deals[How to Cite: Savitri, L. (2013). Land Control and Ideological Struggle: Competing Articulations of âThe Owner of Landâ.Â Journal Of Rural Indonesia, 1(1), 35-54. Retrieved from http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/36]